Profile of OPIOID Dependent Patients - Rastogi, Pali; Rastogi, Deepti (International Journal of Innovative Research in Medical Science, 2018)
Background: The use of opioid is increasing because of illicit drug trafficking, easy availability and decrease in prices. The study attempted to evaluate the profile of opioid dependent patients. Material and method: Patients attending de addiction clinic were evaluated using semi structured proforma and ICD 10 DCR criteria, data was collected and analysed. Results: Only male patients reported. Most of them were young, married, had low education, Hindus, belonged to joint family, low socioeconomic status with rural background. All of them were using tobacco; most of them used other illicit substances before starting opioid. Most of them started under peer pressure, shifted to chasing, continued opioid due to withdrawal symptoms and craving, consulted after many years of consumption under compulsion of family members and financial problems. Conclusion: Addressing psychosocial factors in opioid dependent patients is helpful in their treatment.